Influencing Factors of Students Aged 10–20 Non-participating in Home Physical Exercise During the COVID-19 Isolation Policy Period: A Cross-Sectional Study From China - Luo, Lin; Zeng, Xiaojin; Wu, Yan; An, Fei; Huang, Jiahong; Yang, Hao; Jiang, Quanning; Ou, Qiang; Du, Jianjun; Song, Naiqing (Frontiers in Public Health, 2022)
Background: A number of public health measures are required during the COVID-19 pandemic. To stop the spread of COVID-19, the Chinese government has adopted isolation policies, including closing non-essential businesses, public transportation and schools, moving students’ face-to-face learning to online, and recommending the cancellation of all non-essential activities and outdoor activities. However, while this isolation strategy has reduced human-to-human transmission of COVID-19, it has led to dramatic changes in students' daily lives and learning styles, including reduced physical activity and increased sedentary time. Considering the potentially harmful effects of physical inactivity, this study hoped to explore the incidence and influencing factors of non-participation in home physical exercise among Chinese students aged 10-20 during the implementation of the COVID-19 isolation policy. Methods: Through an online questionnaire platform, this study created an open-ended questionnaire (from March 1, 2020 to March 10, 2020) and distributed it to students in areas where isolation policies were enforced. The questionnaire was initially distributed by 10 recruited volunteers, and then the questionnaire was voluntarily forwarded and shared by the subjects or others, in a "snowball" way, to expand distribution. Finally, the survey data of 4532 Chinese students aged 10-20 were collected. The incidence of respondents non-participating in home physical activity was determined using univariate analysis. Using odds ratios and 95% confidence intervals of a multivariate binary logistic regression model, factors influencing non-participation in home physical exercise were estimated. Results: Among the sample students, the incidence rate of non-participating in home physical exercise was 25.86% (24.06%-27.15%). Exercise intentions, exercise habits, self-assessed health, beliefs in physical health, family exercise, family exercise recommendations, home exercise conditions, school exercise guidance, and health education programs had a negative impact on students non-participating in home physical exercise. Academic performance and electronic product use had a positive effect on non-participating in home physical exercise. Conclusions: A variety of forward leaning factors, enabling factors and demand factors have affected the occurrence of students' non-participating in home physical exercise.. Future health isolation policies should take into account these influencing factors to reduce the occurrence of students' non-participating in home physical exercise .